POLA ASUH ORANG TUA YANG ANAKNYA BERSEKOLAH DI SDN 001 SAWAH BARU KECAMATAN KAMPA KABUPATEN KAMPAR - Mei Dela Sari; Jaspar Jas; Widiastuti Widiastuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine which parenting pattern is most dominantly applied by parents whose children attend school at SDN 001 Sawah Baru Kampa Subdistrict Kampar District. The formulation of the problem of this research is the most dominant parenting pattern applied by parents whose children go to school at SDN 001 Sawah Baru Kampa Kampar District. The population in this study were 55 people. So the researcher use saturated samples so that all the population sampled that is as many as 55 people, and 20 people for sample test questionnaire at SDN 002 Rambai Island Kampa District Kampar District. The type of this research is descriptive with quantitative approach. The data collection instrument is a questionnaire with 45 statements and after the trial there are 40 valid statements to be used as research instruments. Data analysis through quantitative descriptive analysis. The findings of this study indicate that the pattern of parents' care that their children go to SDN 001 Sawah Baru Kampa Kampar District is the most dominant of democratic parenting with a percentage of 70.8%. Keywords: Foster Pattern